DO GENETICALLY RELATED COMET PAIRS AND GROUPS EXIST? - Shestaka, I. S. (Одеські астрономічні публікації, 2017)
In connection with the discoveries of the new comets 1982b and 1982c, 1988e and 1988g, the orbits of which have the essentially similar elements, the problem of existence of the cometary groups with the similar orbits and their genetical relationship are considered. The Similarity of the quasistationary parameters, and the Tisserand invariants Ti is used as a criterion for the selection of comets in the groups. This criterion has been verified on comets of the Kreutz’ family and comets approaching closely the Jupiter. It is shown that this criterion is quite feasible one for selection of comet groups related genetically.